Mediatised Culturalisation Through Television: Second-Generation Alevi Kurds in London - Emre Cetin, Kumru Berfin (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Satellite television has not only provided migrant communities with stronger ties to their home countries but also enabled second-generation migrants in particular to know more about their country of origin beyond their family ties. The aim of this chapter is to explore the ways in which Turkish television contributes towards the making of the transnational identity of the “twice minority” group of Alevi Kurds through what I call mediatised culturalisation. Drawing on 17 in-depth interviews that I conducted with the second-generation members of the Alevi Kurdish community in London in 2016, I explore the role of Turkish television in contesting the boundaries of transnational social imaginaries of the second-generation viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Representing Female Detectives in Turkish Police Procedurals - Kesirli Unur, Ayşegül (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Police procedural has been historically perceived as a dominantly masculine genre for continually revolving around the investigations of male police officers. In accordance with the patriarchal norms that pervade Turkish society, local variations of the police procedural genre have conveniently appropriated this globally known convention and left little room for female detectives in their narratives. However, whenever they got a chance to be included in this male-dominated universe, female detectives have been frequently depicted as relatively independent women but also submitted to the traditional norms of womanhood in an ambivalent manner. This chapter examines this hesitant position of female police detectives in three contemporary Turkish police procedurals, Kanıt (The Evidence, 2010–2013), Cinayet (The Killing, 2014) and Sṃahsiyet (Personality, 2018), by building connections between the interest of police procedural genre in feminist debates in the global context and the influence of this interest on local variations.
Keywords: 1-TV; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Women’s Fragile Trust: Safety, Familiarity, and Secrecy in the Marriage Show - Akınerdem, Feyza (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The marriage show was a popular reality show format that invited people to find their soulmate and marry on live television in Turkey. Based on ethnographic fieldwork which took place in the show’s studio between 2011 and 2012, this chapter explores female participants’ investment of their trust in the show. While being reluctant about finding a spouse on television, women take on registers of safety, familiarity, and secrecy to navigate the show as a safe venue. This endeavor also involved women’s safeguarding of themselves on their way to marriage. The fragility of trust in the show, therefore, indicates how women foresee risks and yet strive for securing happiness and safety in marriage in general. This affective tension, at a larger scale, is related to the increased sense of insecurity at a global scale, and the systematic failure of the family to provide the safe living environment it promises in the Turkish context.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Televised Journalistic Documentaries of the 1990s: The Form, Content, and Historical Juncture - Çelik, Burçe (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The 1990s’ popular televised journalistic/history documentaries have played a vital role in the making of political television culture, society of political spectacle, and the production of popular history and memory in Turkey. Despite their importance, these documentaries did not attract enough scholarly attention. By focusing on arguably the most popular and impactful journalistic/history documentaries of Turkey’s history, developed by Mehmet Ali Birand in the 1990s, I will assess the role of television in teaching, telling, and writing the political history. In doing so, I will also contextualize the form and discourse of these documentary series within historical juncture of globalization and neoliberalization of television as well as the country’s political economy.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Le soft power à l’épreuve de la réception. Le cas des fictions sérielles turques en Grèce - Larochelle, Dimitra Laurence (Réseaux, 2021)
La production de fictions sérielles turques est en constant développement. Ces fictions ont un très grand succès au niveau local (Tanriöver, 2011 ; Öztürkmen, 2018), avant d’être exportées au-delà des frontières turques depuis les années 2000, d’abord dans des pays sous l’influence culturelle de l’ancien Empire ottoman (à savoir les Balkans et le Moyen-Orient, puis au-delà (en Amérique latine, en Chine, au Pakistan, en Inde, au Bangladesh, etc.), faisant de la Turquie un leader mondial en matière de production et d’exportation. La Grèce est devenue un grand consommateur de fictions sérielles turques et les forts taux d’audience que ces dernières y réalisent ont conduit certains chercheurs à débattre du soft power turc. Plus précisément, en se basant sur les activités des fans des feuilletons en question (comme le tourisme en direction de la Turquie), certains ont soutenu que le visionnage des feuilletons turcs entraîne une amélioration des relations gréco-turques (Paris, 2013). En parallèle, de nombreux articles journalistiques, aussi bien en Grèce que dans d’autres pays, analysent le succès de ces feuilletons auprès du public grec comme une réussite diplomatique du gouvernement turc (Moore, 2013 ; Dimitrakopoulos, 2020).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; France (lieu de production du savoir); Grèce (corpus analysé); Turquie (corpus analysé); _Nettoyé

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Carnival of Images : Brazilian Television Fiction - Mattelart, Michèle.; Mattelart, Armand. (Bergin & Garvey, 1990)
In creating and developing the new genre of the televised novela, a one-hour long dramatic serial, the Brazilian television industry grew, in less than 15 years, from an insignificant player in the international market to one of the largest, most influential in the world. In the first book in English to explore the phenomenon of the telenovela Michele and Armand Mattelart challenge accepted views of the world dominance of United States television and probe the socioeconomic impact of this new genre on a third world country. Using the telenovela and its impact on the medium world-wide, the authors document the important changes in the international circulation of television programs and in the way television is perceived theoretically as a subject of research. The book traces the development of the novela in a country that, in the early 1960s, did not have any nationwide media and later--from 1964 to the 1970s--was ruled by a military dictatorship. It further analyzes the formation of the genre and its mode of production, placing the novela's appearance and development in its cultural, institutional, and economic context. The authors look at the peculiar contradictory relation between the genre's creators and developers--generally left wing intellectuals--and the manipulations required to construct a television industry in a highly competitive marketplace. The book begins with a description of the economic, institutional, and cultural context which produced the genre. It explores the world of soap operas, the development of a national television industry, and the beginnings of an urban consumer society in Brazil. The authors include a valuable and detailed study of the mode of production of the telenovela, placing both the form and content of the genre in their specific economic and institutional context. The book goes on to examine the relationship between the genre and its wider social and cultural environment, explaining its immense popularity and the social function it fulfills. Finally, the authors link the study of Brazilian television to wider debates in media and cultural studies.
Keywords: 1-TV; 2-Approches sociologiques; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Brésil (corpus analysé); France (lieu de production du savoir); _Nettoyé